2020
DOI: 10.1017/s0021859620000684
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different sources and levels of tannins on live performance and antioxidant response of Ossimi lambs

Abstract: Pomegranate peels (PP) and mango leaves (ML) were analysed for nutrients and tannin contents. In an in vitro test, ten diets were prepared; six contained 2, 4 and 6% of PP or ML, three diets supplemented with mixed levels of PP and ML (1 + 1%, 2 + 2% and 3 + 3%) and control diet free of them. Gas was measured after 3, 6, 12, 24, 48 and 72 h of incubation. Methane and rumen parameters were estimated. In an in vivo experiment, 40 Ossimi lambs were divided into four groups; the first was control, other groups (T1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…The authors declare no conflict of interest. [20] Brazil CL CT E Dey et al [106] India Ficus infectoria (n = 3) B, B, B N, N, N Abdalla et al [107] Brazil OP, Clep B, B N, N Fernandes et al [14] Brazil Mimosa tenuiflora (n = 3) B, B, B N, N, N Francisco et al [108] Portugal CL (n = 2) CT, CT N, N Girard et al [109] Switzerland LC and OV B, B N, N Guerreiro et al [110] Portugal CL (n = 4) CT, CT, CT, CT, CT N, N, N, N, N Gruffat et al [111] France OV (n = 2) CT, CT N, N Hart et al [112] United Kingdom Pisum sativum (n = 4) CT, CT, CT, CT, CT N, N, N, N, N Hassan et al [113] Egypt Punica granatum, MI, B B, B, B N, N, N Hatami et al [114] Iran Punica granatum (n = 3) B, B N, N Jerónimo et al [115] Portugal VV (n = 2), CL (n = 2) CT, CT, CT, CT, CT E, N, E, N Jerónimo et al [116] Portugal VV (n = 2), CL (n = 2) CT, CT, CT, CT, CT E, N, E, N Kamel et al [117] Saudi Arabia QU (n = 2) CT, CT E, E Kazemi and Mokhtarpour [118] Iran Prunus amygdalus (n = 3) B, B, B N, N, N Leparmarai et al [119] Switzerland VV B E Lima et al [120] Brazil Macrotyloma axillare B N Liu et al [21] China CH (n = 2) HT, HT E, E López-Andrés et al [91] Italy QU CT E Majewska and Kowalik [121] Poland VAC, Quercus sp. B, B N, N Flores et al [122] Brazil VV (n = 3) B, B, B N, N, N Flores et al [123] Brazil VV (n = 3) B, B, B N, N, N Moghaddam et al [124] Iran Berberis vulgaris (n = 2) B, B N, N Natalello et al [18] Italy Punica granatum B N Nobre et al [125] Brazil Psidium guajava (n = 4) B, B, B, B, B N, N, N, N, N Norouzian and Ghiasi [126] Iran Pistacia vera (n = 3) B, B, B N, N, N Obeidat et al [127] Jordan Ceratonia siliqua (n = 2) CT, CT N, N Odhaib et al [128] Malaysia RO (n = 3), NS (n = 3), B (n = 3) B (n = 9) N (n = 9) Pathak et al [13] India B, B CT, CT N, N Peng et al [95] Canada Dalea purpurea CT N Po et al…”
Section: Institutional Review Board Statement: Not Applicablementioning
confidence: 99%
“…The authors declare no conflict of interest. [20] Brazil CL CT E Dey et al [106] India Ficus infectoria (n = 3) B, B, B N, N, N Abdalla et al [107] Brazil OP, Clep B, B N, N Fernandes et al [14] Brazil Mimosa tenuiflora (n = 3) B, B, B N, N, N Francisco et al [108] Portugal CL (n = 2) CT, CT N, N Girard et al [109] Switzerland LC and OV B, B N, N Guerreiro et al [110] Portugal CL (n = 4) CT, CT, CT, CT, CT N, N, N, N, N Gruffat et al [111] France OV (n = 2) CT, CT N, N Hart et al [112] United Kingdom Pisum sativum (n = 4) CT, CT, CT, CT, CT N, N, N, N, N Hassan et al [113] Egypt Punica granatum, MI, B B, B, B N, N, N Hatami et al [114] Iran Punica granatum (n = 3) B, B N, N Jerónimo et al [115] Portugal VV (n = 2), CL (n = 2) CT, CT, CT, CT, CT E, N, E, N Jerónimo et al [116] Portugal VV (n = 2), CL (n = 2) CT, CT, CT, CT, CT E, N, E, N Kamel et al [117] Saudi Arabia QU (n = 2) CT, CT E, E Kazemi and Mokhtarpour [118] Iran Prunus amygdalus (n = 3) B, B, B N, N, N Leparmarai et al [119] Switzerland VV B E Lima et al [120] Brazil Macrotyloma axillare B N Liu et al [21] China CH (n = 2) HT, HT E, E López-Andrés et al [91] Italy QU CT E Majewska and Kowalik [121] Poland VAC, Quercus sp. B, B N, N Flores et al [122] Brazil VV (n = 3) B, B, B N, N, N Flores et al [123] Brazil VV (n = 3) B, B, B N, N, N Moghaddam et al [124] Iran Berberis vulgaris (n = 2) B, B N, N Natalello et al [18] Italy Punica granatum B N Nobre et al [125] Brazil Psidium guajava (n = 4) B, B, B, B, B N, N, N, N, N Norouzian and Ghiasi [126] Iran Pistacia vera (n = 3) B, B, B N, N, N Obeidat et al [127] Jordan Ceratonia siliqua (n = 2) CT, CT N, N Odhaib et al [128] Malaysia RO (n = 3), NS (n = 3), B (n = 3) B (n = 9) N (n = 9) Pathak et al [13] India B, B CT, CT N, N Peng et al [95] Canada Dalea purpurea CT N Po et al…”
Section: Institutional Review Board Statement: Not Applicablementioning
confidence: 99%
“…Introducing G. arborea leaves into small ruminant diets improved protein digestibility [64]. Moreover, M. indica leaves can be used in lambs' rations at a rate of 6% without any harmful effects [65], and B. sapida leaves are easily consumed by goats and have a high digestibility of DM and CP [66]. A study on browse leavf digestibility showed that nitrogen retention was positive for some browse species [67].…”
Section: In Vivo Digestibilitymentioning
confidence: 99%
“…Therefore the use of tannins is highly dependent on the level. The use of tannins as much as 4 g/kg of sheep diet can reduce gas production, increase productivity, and improve digestion and rumen function [29].…”
Section: Tanninmentioning
confidence: 99%